2020
DOI: 10.1016/j.jhazmat.2020.122209
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial cell surface sulfhydryl sites in cadmium detoxification by Pseudomonas putida

Abstract: Highlights • P. putida detoxifies aqueous Cd using cell surface sulfhydryl sites. • Cell surface sulfhydryl site concentrations vary as a function of growth time. • Cell growth with Cd positively correlates to sulfhydryl site concentration. • Cell growth with Cd is independent of the non-sulfhydryl site concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In the LB medium, the MIC of copper was 1.8 mM Cu 2+ , which was much higher than that in the basic medium (Figure 2 and Figure S2). Compared with the basic medium, the LB medium was richer in organic matter and inorganic salts, especially the sulfur‐contain amino acids, which facilitated bacteria to deal with heavy metals (Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the LB medium, the MIC of copper was 1.8 mM Cu 2+ , which was much higher than that in the basic medium (Figure 2 and Figure S2). Compared with the basic medium, the LB medium was richer in organic matter and inorganic salts, especially the sulfur‐contain amino acids, which facilitated bacteria to deal with heavy metals (Yu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the production of H 2 S was significantly inhibited by the amending of Cu 2+ (Figure S4). It has been shown that the formation of copper sulfide (Kimber et al, 2020) or the compound with copper and glutathione (Stewart et al, 2020) could alleviate the biological toxicity of copper, while sulfhydryl groups combined with cations are important ways for Cu 2+ detoxification (Lin et al, 2020; Yu et al, 2020; Yu & Fein, 2016; Zeng et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, sulfate metabolism is associated with bacterial resistance and immobilization of Cd (Zhu et al, 2017). Under Cd stress, bacteria assimilate more sulfate to produce thiol compounds, which are connected to the detoxi cation of Cd in the cell and the immobilization of Cd (Chen et al, 2016;Yu et al, 2020). Thus, increasing the activity of arylsulfatase in the BCM treatment indicated that the addition of biochar and AN-B15 improved the Cd resistance of the soil microbiome and Cd immobilization.…”
Section: Effects Of Strain An-b15 and Biochar On CD Speciation Ph And...mentioning
confidence: 99%
“…Loh and Chua [11] reported complete degradation of 600 mg/L benzoate in 11 h using P. putida ATCC 49451. Li et al [12] performed intergeneric protoplast fusion between P. putida and Bacillus subtilis to enhance benzoate tolerance as high as 10,000 mg/L with a specific growth rate of 30.9 × 10 -3 h. Yu et al [13] conducted the bacterial metal detoxification systems to observe the role of P. putida cells surface sulfhydryl sites in the detoxification of Cd. Their experimental results found that P. putida cells could detoxify Cd concentrations of 5 and 20 mg/L.…”
Section: Introductionmentioning
confidence: 99%